Android application for wireless acquisition and visualization of biomedical signals - Rafael Esmildo Smith-Colás; Bárbaro Nicolás Socarrás-Hernández; Carlos Román Vázquez-Seisdedos (Revista Información Científica, 2022)
Introduction: technological advances experienced by phones and tablets with Android operating system have enabled the development of countless applications in the field of medicine. As far as we know, there is not reported in our health system the use of a portable device that allows the specialist to wirelessly monitor remotely the biomedical signals associated with the patient.